Mahen’s song ‘Pura-pura Lupa’ in English by Emma Hesters: Translation Techniques, Methods, and Ideologies Analysis - Muhammad Saiful Mukminin; Evi Iryani (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
Song translation presents unique challenges due to the intricate relationship between lyrics, melody, rhythm, and cultural meaning. The present research aims to analyze the translation techniques, methods, and ideology in the song Pura-pura Lupa by Mahen, which was translated into English by Emma Hesters. The present research employs the theoretical frameworks of translation techniques (Molina and Albir, 2002), translation methods (Newmark, 1988), and translation ideology (Venuti, 1995). A descriptive qualitative method with a product-based translation approach is used. The results of the present research show that six types of translation techniques are used, i.e. discursive creation, established equivalence, amplification, compensation, reduction, and linguistic amplification, with discursive creation being the most dominant. Since all the identified translation techniques are oriented towards the target language, the translation method also tends to support adaptation into the target language. Therefore, the translation ideology applied in this song refers to domestication. The research implies that song translation needs creative adjustments for acceptance in the target culture and language, though this may alter the original message’s authenticity. The present research offers practical guidance for song translators and music industry professionals on translation and localization strategies, while theoretically expanding the understanding of translation techniques and confirming the dominance of domestication in cross-cultural song adaptation.